Immunology and human reproduction. - Huamán Elera, José (2015)
Immunology becomes for us Gynecology Obstetricians, knowledge somewhat difficult to learn, as perhaps it would be for the inmunálogo understand the mechanism of breech delivery and adjustments to flawed pelvis; but modern and far-reaching participation of this branch of medicine in gynecology and obstetrics, forcing us to study it, understand it and apply in our specialty, as we did with the physiology and biochemistry, when Saling spoke of acid-base balance diagnosis and treatment of fetal distress microanalysis using blood during labor. Also knowledge and dissemination of the influence of hormones in human reproduction brought us intimately Endocrinology, initially allowing quick and easy detection of pregnancy and later for assessment of fetal wellbeing and placental function.